Analisis Kesulitan Siswa Dalam Proses Pemecahan Masalah soal cerita bilangan pecahan kelas V SD Negeri Karangtempel Semarang - Julia Intan Permatasari; Husni Wakhyudin; Fajar Cahyadi (Universitas PGRI Adi Buana Surabaya, 2021)
The purpose of this study was to determine the existence of learning difficulties experienced by students of SD Negeri KarangTempel seen in the ability to solve mathematical problems in the subject of Fractions and determine the factors that affect the ability to solve mathematical problems of fraction material in fraction numbers of grade V SD Negeri KarangTempel Semarang. This research uses qualitative methods with a descriptive approach. Data collection in the study was carried out by means of observation, questionnaires, questions, interviews and documentation. Based on the results of research at SD Negeri Karang Tempel, there are learning difficulties in Fraction Numbers material seen from the ability to solve mathematical problems. The results of the research were as follows: (1) difficulties in learning to solve mathematical problems in the material of Fractions including: difficulties in understanding problems, difficulties in planning solutions, difficulties in implementing plans, and difficulties in re-examining or drawing conclusions. (2) factors that influence learning difficulties in solving mathematics problems include factors from the school environment and the family environment. Based on this research, the advice given to the teacher is to pay more attention to students who have difficulty learning math problem solving, especially Fraction material, besides that the teacher should use a variety of media or methods so that students are interested and don't feel bored. Suggestions to students when working on questions should not be in a hurry so as not to experience errors in working on questions laterstudents should be more active in asking questions during learning activities so that they don't make mistakes again in working on multiplication problems.